NAVIGATING THE CHALLENGES AND OPPORTUNITIES OF THE WTO'S TRADE FACILITATION AGREEMENT IN INDONESIA - Maulana, Mursal; Adolf, Huala (Universitas Syiah Kuala, 2024)
The Trade Facilitation Agreement (TFA) is a significant multilateral trade accord adopted by the World Trade Organization (WTO) to streamline the movement, release, and clearance of goods. Indonesia ratified the TFA through Law No. 17 of 2017 and has implemented 87.7% of its Category A commitments, along with 11.3% of Category B commitments. Despite this progress, Indonesia faces challenges such as regulatory complexities, bureaucratic inefficiencies, coordination issues, and technical constraints. This article explores these challenges and the potential economic benefits of fully implementing the TFA, especially in Indonesias international trade. Using a juridical-normative approach, the article identifies key issues that need to be addressed, including legislative harmonization, streamlined bureaucratic processes, improved digital infrastructure, and better coordination in trade facilitation governance. It also highlights the advantages of the TFA, such as reduced trade barriers, increased efficiency, and enhanced global competitiveness. To overcome existing challenges and maximize the benefits of TFA implementation, Indonesia should focus on regulatory harmonization, inter-agency coordination, and upgrading digital trade infrastructure. Strengthening the National Trade Facilitation Committee (NTFC), modernizing customs automation, and expanding the Indonesia National Single Window (INSW) will improve efficiency and lower costs, thereby solidifying Indonesia's position in the global trading system.